Contribution of Arbuscular Mycorrhizal Fungi, Phosphate–Solubilizing Bacteria, and Silicon to P Uptake by Plant - Etesami, Hassan; Jeong, Byoung Ryong; Glick, Bernard R. (Frontiers in Plant Science, 2021)
Phosphorus (P) availability is usually low in soils around the globe. Most soils have a deficiency of available P; if they are not fertilized, they will not be able to satisfy the P requirement of plants. P fertilization is generally recommended to manage soil P deficiency; however, the low efficacy of P fertilizers in acidic and in calcareous soils restricts P availability. Moreover, the overuse of P fertilizers is a cause of significant environmental concerns. However, the use of arbuscular mycorrhizal fungi (AMF), phosphate–solubilizing bacteria (PSB), and the addition of silicon (Si) are effective and economical ways to improve the availability and efficacy of P. In this review the contributions of Si, PSB, and AMF in improving the P availability is discussed. Based on what is known about them, the combined strategy of using Si along with AMF and PSB may be highly useful in improving the P availability and as a result, its uptake by plants compared to using either of them alone. A better understanding how the two microorganism groups and Si interact is crucial to preserving soil fertility and improving the economic and environmental sustainability of crop production in P deficient soils. This review summarizes and discusses the current knowledge concerning the interactions among AMF, PSB, and Si in enhancing P availability and its uptake by plants in sustainable agriculture.